Manhaj Tafsir Bahrul Muhith Abu Hayyan Al-Andalusiy - Restu Ashari Putra; Andi Malaka (UIN Sunan Gunung Djati Bandung, 2022)
Abu Hayyan Al-Andalusiy compiled his interpretation in a very distinctive way through a linguistic approach as well as a steady and free interpretation. But on the one hand he rejects the categorization of interpretations carried out scientifically and bil ra'yi. This paper is structured to review how Abu Hayyan's method in parsing the interpretation of his work in the book of Bahrul Muhith analytically so that a pattern of his interpretation method is found, especially in relation to the category of special methods of interpreting the perspective of Abu Hayyan Al-Andalusy.